Black Box Testing on the Wingpos Website Using the Equivalence Partitioning Technique - Nadhifah, Jauza; Muhammad Al Amin; Capriandika Putra Susanto; Muhammad Galuh Gumelar; Anka Luffi Ramdani; Mindara, Gema Parasti; Wicaksono, Aditya (Asosiasi Riset Teknik Elektro dan Infomatika Indonesia, 2025)
In the digital business environment, web-based Point of Sale (POS) systems play a vital role in supporting transaction processing, inventory management, and operational decision-making. Ensuring the functional reliability of such systems is essential, particularly in critical authentication features that regulate user access. However, undetected functional errors within login and registration modules may disrupt operations, compromise data integrity, and reduce user experience quality. Therefore, this study aims to evaluate the functionality of the Wingpos website, focusing specifically on the login and registration features. The research applies the Black Box Testing approach using the Equivalence Partitioning technique, which enables systematic functional validation by classifying input data into representative valid and invalid partitions without requiring access to source code. The testing process involved designing structured test cases, executing input scenarios, and comparing actual system outputs with expected results. The findings reveal that most authentication processes function in accordance with system specifications, as seven out of ten test scenarios produced expected outcomes. Nevertheless, three discrepancies were identified, including inconsistent error message validation in the login feature and the system’s inability to properly verify invalid email domains during registration. These results indicate that while the system demonstrates general functional reliability, certain validation mechanisms require refinement. In conclusion, the application of Black Box Testing with the Equivalence Partitioning technique proves effective in identifying functional gaps and supporting quality assurance processes in web-based POS systems, particularly in strengthening authentication feature reliability and improving overall system performance